Rapid Determination of Pemetrexed Concentration and Distribution in Human Breast Cancer Cells (McF-7) Based on UHPLC-MS/MS - Mengwei Zhang; Zhipeng Wang; Qiqiang Zhang; Qing Ye; Fengjing Xu; Lili Cui; Yanping Liu; Shouhong Gao; Wansheng Chen; Yan Liu (International Journal of Analytical Chemistry)
Cell is the basic unit of structure and function of all living bodies. The study of intracellular drug concentration distribution is helpful to understand the drug efficacy of target site. Pemetrexed is a new multitarget folate antagonist with pyrrolidine group as its core structure. An ultra high-performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS) method was developed for rapid quantification of pemetrexed concentration in human breast cancer cells (MCF-7). Sample pretreatment was completed by protein precipitation using methanol. The optimized chromatographic separation was achieved on a ZORBAX SB-C18 column (2.1 × 150 mm, 3.5 μm). The column was equilibrated with initial mobile phase and eluted under gradient phases containing 0.1% formic acid in water (phase A) and in acetonitrile (phase B). The gradient program started at 5% B, increased to 95% B in 2 min, and then held at 95% B for 1.5 min. The linear range of pemetrexed in cells and nucleus was 2.0–200.0 ng/mL, while in the medium sample it was 50.0–5000.0 ng/ml, and the correlation coefficients were all greater than 0.99. The recovery was 47.50–67.55% (2.0–200.0 ng/mL) and 82.72–97.15% (50.0–5000.0 ng/mL), and the matrix effect was 98.10–100.62% (2.0–200.0 ng/mL) and 89.78–97.65% (50.0–5000.0 ng/mL). Interday precision and intraday precision (RSD%) were less than 15.0% (for LLOQ, less than 20%), and accuracy (RE%) was within ±15%; the deviation of stability was within ±15%, all meeting the requirements of biological sample analysis. The results of intracellular samples showed that the concentration of pemetrexed reached its peak at 3 h after administration. The concentration of pemetrexed in the nucleus continued to increase 2 h after administration and may have reached the maximum concentration at 6 h.